Patterns of postpartum oestrus onset and associated plasma progesterone profiles in Bos indicus cows in Ethiopia - Mukasa-Mugerwa, E.; Tegegne, Azage; Ketema, H. (Elsevier, 1991)
Presents the results of a study designed to characterize further the temporal patterns of oestrus onset and plasma progesterone profiles during the postpartum ovarian activitity in two groups of Ethiopian Bos indicus (Zebu) cows whose calves were either weaned at 4.5 months or at 7.5 months; reports that the postpartum anoestrous interval (PPAI) differed significantly between groups and was affected by dam body condition score but not by calf sex, calf age or dam weight at weaning; and concludes that if the reproductive efficiency of Zebu cows is to be improved, cows must be managed to calve and maintain adequate body condition, calves weaned early and oestrus detection efficiency be improved under artificial insemination programmes.